2019
DOI: 10.1186/s12879-019-4279-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between the vaginal microbiome and high-risk human papillomavirus infection in pregnant Chinese women

Abstract: Background: In this study, the association between high-risk human papillomavirus (hrHPV) infection and the vaginal microbiome in pregnant women was evaluated in Chinese cohorts. Methods: The vaginal bacterial composition of four groups, 38 hrHPV-infected pregnant women (PHR, n = 38), pregnant women without HPV infection (PN, n = 48), nonpregnant women with hrHPV infection (NPHR, n = 19) and nonpregnant women without HPV infection (NPN, n = 30), was characterized by deep sequencing of barcoded 16S rRNA gene fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 52 publications
11
42
2
Order By: Relevance
“…Although there were no signi cant relative abundance differences of the top 10 bacterial genus, which totally account for 96.25% microbe amount of the whole community, between pregnant and non-pregnant women, we observed the decreased microbial richness measured by PD_whole tree alpha diversity in pregnant than in nonpregnant women and in normal than in infected women. This result are contrary to recently reported by Yulian Chen,et al [11] in that they found both pregnancy and HPV infection can increase vaginal bacterial microbial richness and diversity. Although we consider the reason is they measured the microbial richness by Chao and Shannon index other than we used PD_whole tree that focus on the phylogenic a nity between each microbe, there must exist underlying factors that shield the real association of taxonomic diversity to pregnancy.…”
Section: Discussioncontrasting
confidence: 99%
“…Although there were no signi cant relative abundance differences of the top 10 bacterial genus, which totally account for 96.25% microbe amount of the whole community, between pregnant and non-pregnant women, we observed the decreased microbial richness measured by PD_whole tree alpha diversity in pregnant than in nonpregnant women and in normal than in infected women. This result are contrary to recently reported by Yulian Chen,et al [11] in that they found both pregnancy and HPV infection can increase vaginal bacterial microbial richness and diversity. Although we consider the reason is they measured the microbial richness by Chao and Shannon index other than we used PD_whole tree that focus on the phylogenic a nity between each microbe, there must exist underlying factors that shield the real association of taxonomic diversity to pregnancy.…”
Section: Discussioncontrasting
confidence: 99%
“…All enrolled women were preliminarily screened by both an HPV genotyping test and the ThinPrep cytology test (TCT), using a commercial HPV genotyping kit as previously described [25]. TCT results were categorized according to Bethesda System criteria [26].…”
Section: Study Population and Sample Collectionmentioning
confidence: 99%
“…A Chinese study identified several microbial genera in hrHPV-infected women (Bifidobacterium, Bacillus, Megasphaera, Sneathia, Prevotella, Gardnerella, Fastidiosipila, and Dialister), while another set (Bifidobacterium, Megasphaera, Bacillus, Acidovorax, Oceanobacillus, and Lactococcus) in hrHPVinfected pregnant women. In pregnancy, this study showed an association between a more diverse cervical microbiota and HPV (125). In addition, several genera and species were associated to HPV positivity (Ureaplasma parvum), HPV negativity (Brochothrix, Diplorickettsia, Ezakiella, Faecalibacterium, and Fusobacterium), likelihood of reinfection (Actinomyces) or persistence (Prevotella, Dialister, and Lachnospiraceae) (126).…”
Section: Preconceptional Period (Genital Tract Infections)mentioning
confidence: 63%